2000
DOI: 10.1016/s0891-5849(99)00195-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress involvement in chemically induced differentiation of K562 cells

Abstract: The erythroid differentiation of K562 cells could be achieved by exposure to several pharmacologic agents, including hemin, butyric acid (BA), and anthracycline antitumor drugs such as aclarubicin (ACLA) and doxorubicin (DOX). When used at subtoxic concentrations, these drugs induce the overexpression of erythroid genes, leading to hemoglobinization of cells. Because anthracyclines are known to generate oxidative damage, we intended to demonstrate the involvement of an oxidative stress in the chemically induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 37 publications
3
51
0
2
Order By: Relevance
“…The ferritin H ARE comprises two copies of bidirectional AP1 motifs (68). Since (i) oxidative stress was shown to be involved in erythroid differentiation of K562 cells (18,47), (ii) hemin induces oxidative stress (54), and (iii) the human ferritin H ARE (at the Ϫ4.5kb region) is within the Ϫ5.2kb to Ϫ4.0kb region in which we identified a hemin-responsive element (Fig. 2a), we hypothesized that the hemin-responsive element is identical to the ARE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ferritin H ARE comprises two copies of bidirectional AP1 motifs (68). Since (i) oxidative stress was shown to be involved in erythroid differentiation of K562 cells (18,47), (ii) hemin induces oxidative stress (54), and (iii) the human ferritin H ARE (at the Ϫ4.5kb region) is within the Ϫ5.2kb to Ϫ4.0kb region in which we identified a hemin-responsive element (Fig. 2a), we hypothesized that the hemin-responsive element is identical to the ARE.…”
Section: Resultsmentioning
confidence: 99%
“…Given several lines of evidence showing that oxidative stress is involved in chemically induced differentiation of K562 cells (18,47), we have tested our hypothesis that ferritin mRNA induction during hemin-mediated K562 differentiation is transcriptionally regulated through the far-upstream ARE enhancer element. In this study, we have found that (i) a heminresponsive element of the ferritin H gene is identical to ARE, (ii) hemin treatment induced binding of cJun, JunD, FosB, and Nrf2 transcription factors to the ferritin H ARE, and (iii) redox factor 1 (Ref-1) is involved in the activation of ferritin H transcription through the ARE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The above results indicated that pO 2 directly affected CD34 + cells expansion and differentiation by modulating ROS-generating NADPH oxidase, and progenitor characteristics of CD34 + cells preserved by hypoxia may due to the lower ROS levels. ROS promoted blood cell differentiation, including monocytic differentiation of HL60 cells (Yang and Shaio, 1994) and erythroid differentiation of K562 cells (Chenais et al, 2000). Heinrich Sauer and coworkers have shown that ROS played a key role in cardiomyocyte differentiation of embryonic stem cells by inducing signaling cascades (Sauer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, H 2 O 2 as well as ROS generating ionizing radiation, hyperoxia and chemical compounds have been demonstrated to promote cell differentiation, e.g. erythroid differentiation of K562 cells [15], monocytic differentiation of HL60 cells [16], neuronal differentiation of PC12 cells [17], osteoclastic differentiation of HD-11EM cells [18], as well as cardiomyocyte differentiation of embryonic stem cells [19]. On the other hand, overexpression of catalase [20] and MnSOD [21] has been demonstrated to inhibit cell proliferation which supports the notion of endogenous ROS as "life signals" which maintain the growth of cells.…”
Section: Introductionmentioning
confidence: 99%